2009
DOI: 10.1016/j.jinteco.2008.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy and welfare in a small open economy

Abstract: This paper characterizes welfare in a small open economy and derives the corresponding optimal monetary policy rule. It shows that the utility-based loss function for a small open economy is a quadratic expression in domestic inflation, output gap and real exchange rate. In contrast to previous works, this paper demonstrates that welfare in a small open economy, completely integrated with the rest of the world, is affected by exchange rate variability. Consequently, the optimal policy in a small open economy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
164
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(177 citation statements)
references
References 41 publications
(23 reference statements)
8
164
3
Order By: Relevance
“…To show the importance of the counter-cyclical risk premium, we report results for the first-order approximation, which wipes out the risk premium from UIP, and for the third-order approximation, which preserves time variation in the risk premium. 1 An alternative route for introducing risk premium in the UIP condition is by building in incomplete financial markets, as in Schmitt-Grohé & Uribe (2003), Turnovsky (1985), Benigno (2009) andDe Paoli (2009). Under incomplete markets, deviations from UIP come from costs of adjusting holdings of foreign bonds.…”
Section: Introductionmentioning
confidence: 99%
“…To show the importance of the counter-cyclical risk premium, we report results for the first-order approximation, which wipes out the risk premium from UIP, and for the third-order approximation, which preserves time variation in the risk premium. 1 An alternative route for introducing risk premium in the UIP condition is by building in incomplete financial markets, as in Schmitt-Grohé & Uribe (2003), Turnovsky (1985), Benigno (2009) andDe Paoli (2009). Under incomplete markets, deviations from UIP come from costs of adjusting holdings of foreign bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since Obstfeld and Rogoff (2000) have classified home bias in consumption puzzle as one of their proposed six puzzles, (Note 1) subsequent studies on macroeconomics could be divided into two main streams, namely, the study on the causes and the effect of home bias in consumption, and the study on the effect of home bias in consumption on the establishment of the optimal economic policy. Literatures in the past showed that cost of transportation (Obstfeld and Rogoff, 2000;Ried, 2009), the size of the economic, the degree of openness (Sutherland, 2005;De Paoli, 2009), non-traded goods (Stockman and Dellas, 1989;Pesenti and Wincoop, 2002;Collard et al, 2007) and intermediate input factors (Hillberry and Hummels, 2002) have been extensively recognized as the main causes for home bias in consumption. In the studies of the effect of consumption home bias, Pierdzioch (2004) presented an analysis of the impact of monetary shock on different degree of consumption home bias and capital mobility, Hau (2002), Pitterle and Steffen (2004), Kollmann (2004), Sutherland (2005), Leith and Lewis (2006), and Cooke (2010) studies on the influence of consumption home bias on the exchange rate; De Paoli (2009) discussed the extent of consumption home bias and the welfare effect of monetary policy.…”
Section: Introductionmentioning
confidence: 99%
“…smaller) expenditure-switching effects with respect to financial autarky to provide insurance over relative marginal utilities of consumptions, an outcome achieved by having larger (resp. smaller) fluctuations in the real exchange rate (see de Paoli [2009]). …”
Section: Introductionmentioning
confidence: 99%